Alvares de Azevedo: a Fantasy Drama - Prado, Décio de Almeida (Revista do Instituto de Estudos Brasileiros, 1995)
Taking as a starting point the duality in Alvares de Azevedo´s life, for he has been considered "both angel and devil", this essay deals with two of his textes connected directly with the theatre. From these, the author has tried to draw a possible outline of his poetics, at the same ime showing the young poets extensive readings on poetry, philosophy and drama, with a keen interest in great playwights, such as Shakespeare. Finally, the essay emphasizes the poets extreme romanticism which will be delected in Macário, the most romantic Brazilian play.